Solid waste management in Barangay UP Campus effect of the plastic bag reduction ordinance and residents' perception towards waste management - Gamboa, Joanna M.; Huelva, Craig T.
The main purpose of the study is to reassess the current solid waste management system of Barangay UP Campus following the implementation of the Plastic Bag Reduction ordinance by the Quezon City government. The assessment involved quantifying the waste generation rate, characterizing the waste generated in terms of composition and volume. The community's compliance to the existing laws and ordinances was also evaluated. A Waste Analysis and Characterization Study (WACS) was performed for selected clusters of the community, taking random samples for biodegradable wastes and non-biodegradable waste. The results before and after the implementation of the plastic reduction ordinance were compared in order to quantify the effectiveness of the ordinance. It was found out that the barangay produces an average of 39860 kg of waste every week with an average daily generation of .25 kg/cap; 42% greater than the 2012 generation rate of 0.180kg/cap. The results of the comparison showed a 42.28% decrease in the amount of plastic generated during the non- biodegradable waste collection on Thursday and a 25.94% decrease during the non-biodegradable waste collection on Saturday. Based on the perception survey conducted, of the 2587 respondents, 70.4% claim that they always practice waste segregation 13.66%, claim they sometimes practice segregation, while the rest claim they never segregate. Only 47% recycle their waste, of which only 52% recycle plastic bags and containers, 7.38% of respondents are very satisfied with the solid waste management in their respective communities, 17.23% are fairly satisfied, while the rest are not satisfied. It has been observed that the ordinance has a significant effect on the amount of waste generated by the barangay one year after its implementation. However, the barangay is still lacking in terms of efficient waste segregation and recycling. A set of recommendations were formulated for the improvement of the waste management system, especially in areas that are of low compliance.